A Literature Review:Perspective of Unique Value Proposition - Hurriyati, Ratih; Disman, Disman; Gaffar, Vanessa; Lisnawati, Lisnawati (Business Education Program of Universitas Pendidikan Indonesia, 2021)
This study aims to determine the dimensions of unique value proposition in various academic literatures that have been published previously. To do so, a systematic review of the unique value proposition literature is conducted. Following previously established inclusion and exclusion criteria for selection a total of 39 journal articles publish in the period 2010 to 2021 are analysed. Ten definitions of unique value proposition are found in the literature, and a unified definition of the construct is advanced. The dimensions of unique value proposition are analysed, and the main differences of the construct with other concepts are also clarified.